Teaching Approaches for Fostering Critical and Analytical Skills in Financial Accounting: A South African School Perspective - Walusa, Ajuma; Mahlomaholo, Qhosola (Technium Education and Humanities, 2025)
Developing critical and analytical skills is vital for success in financial accounting education. These skills help learners understand complex financial concepts and apply them in real-life situations. This article explores different teaching methods used in South African schools to encourage critical and analytical skills in financial accounting classes. By reviewing literature and conducting qualitative research in selected schools, the study highlights effective teaching strategies, such as problem-based learning, collaborative learning, Technology-Enhanced learning and Socratic questioning. The findings reveal that while traditional teaching methods remain the most common approach in educational settings, the adoption of interactive and learner-centered strategies significantly enhances learners' critical thinking and analytical skills. These modern techniques encourage active participation and engagement, allowing learners to explore concepts more deeply and apply their knowledge in practical scenarios. However, the article also highlights several challenges that teachers face when trying to implement these innovative methods. Key obstacles include limited instructional time, curriculum coverage, and the need for in-depth teaching of accounting concepts. Many educators feel unprepared to move away from traditional methods, which can hinder their ability to effectively engage learners and promote critical thinking and analytical skills. To address these issues, the article recommends several essential modifications. It advocates for ongoing professional development opportunities for teachers, urging schools to invest in training programs that focus on innovative teaching strategies, particularly those that improve critical thinking. Additionally, it promotes collaboration between schools, universities, and local businesses to provide resources and support for education, as well as encouraging learners engagement through methods that enhance participation and interaction among learners, such as collaborative discussions and debates.